An unusual contrast-induced encephalopathy following percutaneous coronary intervention in patients with cerebrovascular abnormalities: A case report - Liao, Jiangquan; Wang, Yan; Shao, Mingjing; Wang, Yanling; Du, Jinhang; Li, Xianlun; Yang, Peng; Fu, Dongliang; Dong, Zhe; Liu, Mengru (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Contrast-induced encephalopathy (CIE) is a complication associated with administration of iodinated contrast, which usually happens minutes to hours after contact of contrast, and fully recovers within 72 hours. The clinical manifestations of CIE are diversed, and the pathological mechanism is not explicit. Methods: We report the case of a 66-year-old female who suffered from a delayed CIE following administration of iodinated contrast agent. Symptoms were severe. Imaging examination, biochemical and etiological detection were performed timely. The course of neurological symptoms was atypical. Her complex complications of hypothyroidism and cerebrovascular abnormalities contributed more challenges, which were also clues to the diagnosis. With prompt and active treatment, patient recovered fully over 10 days. Discussion: The diagnosis standard of CIE highly depends on the association with the contact of contrast and the exclusion of other nervous system diseases. Complicated clinical circumstances and individual specificity can lead to different clinical manifestations of CIE, making it even more difficult to diagnose and treat. Prompt and dynamic imaging examination would provide great value in the diagnosis and evaluation of CIE. Timely diagnosis and intervention may be the key to its satisfying prognosis.